Evaluation of intravenous and subcutaneous administration of a novel, excipient‐free, nanoparticulate formulation of paclitaxel in dogs with spontaneously occurring neoplasia. (4th September 2018) - Selting, Kim A.; Bechtel, Sandra M.; Espinosa, Jahna; Henry, Carolyn J.; Tate, Deborah; Bryan, Jeffrey N.; Rajewski, Lian; Flesner, Brian K.; Decedue, Charles; Baltezor, Michael
Abstract : Carriers used to solubilize taxane chemotherapy drugs cause severe hypersensitivity. Nanoparticle formulations can provide improved dissolution and bioavailability of taxanes. Thus, a nanoparticulate, excipient‐free formulation of paclitaxel (CTI52010) was evaluated in tumour‐bearing dogs with intravenous and subcutaneous delivery. Tumour‐bearing dogs were treated with intravenous CTI52010 using a modified rapid dose escalation scheme. Subcutaneous administration was then planned for a small cohort of dogs for comparison. For both groups, serial blood samples were collected after first dosing for pharmacokinetic analysis by LCMSMS. Tumour response was measured using RECIST criteria. Toxicity was recorded using VCOG‐CTCAEv1.1. Fifteen dogs were treated with intravenous delivery at increasing dosages (80‐136 mg/m 2 ), with one objective response in the urethral component of a prostatic carcinoma (probable transitional cell carcinoma) and four dogs with durable stable disease (two carcinomas, two sarcomas). Pharmacokinetic data indicate a rapid initial clearing of the drug from serum followed by an extended elimination half‐life, similar to normal dogs and suggesting reticuloendothelial clearance. Parameters and toxicity were highly variable and a maximally tolerated dosage could not be reliably confirmed. Three dogs were treated with subcutaneous delivery and no drug was detected in circulation, resulting in termination of the study. This novel formulation of paclitaxel is well tolerated in dogs and no unique toxicity or hypersensitivity was noted. The preliminary responses suggest biologic activity. The lack of systemic absorption after subcutaneous administration suggests a possible role for intratumoural anticancer therapy.